(untitled) (American Journal of Technology and Applied Sciences, 2026)
The article analyzes scientific works of both domestic and foreign authors devoted to the study of deformation and destruction of composite materials, and presents a review of scientific and technical literature devoted to the study of the processes of deformation and destruction of composite materials. Considerable attention is also paid to the wide range of test methods used to determine the strength properties and mechanical characteristics of composite materials.